(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2014)
Stature is one of the important criteria for identification. Estimation of stature has special importance when a dead body is found in the mutilated or dismembered state. In present study, attempt is made to reconstruct stature by percutaneous measurement of forearm and hand. A total 180 healthy medical students (90 male and 90 female) of SRG Hospital and Medical College, Jhalawar, Rajasthan were included in study. All students belonged to 18-25 age group. Measurements of stature and left forearm and hand were taken. They were statistically analysed to determine the correlation between stature and length of forearm and hand.